ECTOPIC THYROID IN CHILDHOOD - Nina Cerkvenik; Klemen Dovč; Irena Hočevar Boltežar; Primož Kotnik (The Society for Children with Metabolic Disorders, 2020)
Ectopic thyroid gland is a rare clinical entity characterized by thyroid tissue in a location other than its normal anatom- ical position. It is a developmental abnormality. The most frequent location of ectopic thyroid is at the base of the tongue, although it can be found elsewhere along the path of thyroid embryogenic descent and even at distant body locations. Single ectopy is the most common, but dual and triple ectopy has also been described. Most people with ectopic thyroid are asymptomatic. If symptoms occur, they are related to the location and size of the ectopic tissue as well as its endocrine dysfunction. The most important diagnostic procedure for detection of ectopic thyroid tissue is scintigraphy. For patients with- out symptoms, no treatment is necessary, but they need regular follow-up and action if symptoms appear. Patho- logical changes can occur in the ectopic as in the ortho- topic gland. We present a rare case of dual ectopy with subclinical hypo- thyroidism in a two-and-a-half-year-old girl and a review of cases of ectopic thyroid diagnosed in a 5-year period at the University Children's Hospital Ljubljana.